Chronic Stanford type A aortic dissection manifesting as systemic inflammatory disorder - Kogan, Yana; Slobodin, Gleb; Lurie, Michael; Croitoru, Simona; Elias, Nizar; Odeh, Majed (International Journal of Research in Medical Sciences, 2016)
Typical presentation of type A aortic dissection usually encompasses severe acute chest pain, frequently radiating to the upper back, which is seen in more than 80% of the patients, while isolated back or abdominal pain have been repeatedly reported as the first manifestation of the disease as well. Occasionally, dyspnea due to acute aortic regurgitation, syncope, or stroke, secondary to obstruction of major cerebral vessels, have also been described at presentation of type A aortic dissection. Presentation of aortic dissection as a prolonged systemic illness with a number of nonspecific clinical and laboratory findings, such as low-grade fever, fatigue, malaise, weight loss, anemia, elevated acute phase response laboratory parameters, and absence of any of typical clinical features of the dissection syndrome has been only rarely reported. We describe a patient with type A chronic aortic dissection, manifesting as a systemic inflammatory disorder in the absence of acute chest syndrome. The diagnosis was made accidentally by computed tomography, ordered in the course of the regular work up. The patient underwent emergent surgery with resection and grafting of the dissected aorta. Pathological investigation demonstrated intense acute inflammation with neutrophilic infiltration in the vicinity of the intramural hemorrhage and necrosis, as well as granulation tissue with new vessels formation and collagen deposition in the outer media. The possible pathogenic mechanisms of the phenomenon are discussed.